SPMI Supervision in 2 Islamic Elementary Schools in Jakarta - Yuyun Nuriah; Dalmeri Dalmeri (International Journal Labs, 2022)
The ultimate goal of education management is the quality of graduates as set out in the National Education Standards. Each Education Unit leads to quality improvement in indicators as set in 8 Education standards. The government requires every Education unit to carry out education quality assurance and applied it in the implementation of the Internal Quality Assurance System which includes 5 cycles of constantly and continuously activities that known as PDCA. Nevertheless, in general, the Education Unit does not implement the quality assurance system because it has not been thoroughly socialized by the Government or related institutions. Therefore, efforts are needed to provide assistance in the form of education and training in the Education Unit in implementing the Internal Quality Assurance System (known as SPMI in Indonesia). With SPMI Assistance to the Education Unit, the education unit will understand how to self- evaluate, aware of the shortcomings of each indicator in each education standard, schools will try to meet these lacking indicators constantly and continuously which in the future will form a Quality Culture in the Education Unit.